Analisis Penerapan Metode ATC/DDD dan DU90% Dalam Penggunaan Antibiotik Pada Pasien Rawat Inap Rumah Sakit Stella Maris Makassar - Arsyad, Rival Al-fazri; Pakaya, Mahdalena Sy.; Paneo, Mohamad Aprianto; Rasdianah, Nur; Madania, Madania (Universitas Negeri Gorontalo, 2026)
The antimicrobial resistance (AMR) crisis poses a serious threat to global health, making the rational use of antibiotics a priority within Antimicrobial Stewardship (AMS) programs. This study aims to evaluate the patterns and quantity of antibiotic use among inpatient populations at Stella Maris Hospital Makassar using the Anatomical Therapeutic Chemical (ATC) classification, Defined Daily Dose (DDD), and Drug Utilization (DU) 90% methods. This research employed a retrospective descriptive observational design using medical record data of patients who received antibiotic therapy from October to December 2024. The analysis was conducted by calculating DDD per 100 patient-days and identifying antibiotics contributing to 90% of total use. The results showed eight types of antibiotics were utilized. The three antibiotics with the highest DDD/100 patient-days were Cefuroxime (13.43), Ceftriaxone (11.8), and Cefotiam (10), which, together with Moxifloxacin, were included in the DU 90% segment. The predominance of second-generation cephalosporins—particularly among diagnoses such as unspecified fever, bronchiectasis, typhoid, and bronchitis—indicates a tendency toward broad-spectrum empirical therapy in chronic pulmonary conditions such as COPD and bronchiectasis. In conclusion, antibiotic use at Stella Maris Hospital Makassar is dominated by the cephalosporin class, highlighting the need for ongoing evaluation and strengthened implementation of AMS programs to optimize antibiotic therapy, improve treatment effectiveness, and reduce the risk of increasing antimicrobial resistance at the hospital level.